How do my students think about ME as an English-language teacher?. Issue 6 (1st November 2016) - Tohidian, Iman
Abstract: The concepts of student-centered classrooms, empowering students with communicative competences to be able to voice their ideas in the surrounding community, powerless and marginalized strata, are conspicuous and prevalent in recent research articles. Teachers are well-acquainted with pertinent underpinnings and theories of teaching methodologies; and some research is also conducted to see how those learned theories in pre-service and in-service programs are implemented in their real-life classrooms. But, the teachers' reflection on implementation of their teaching practices in classrooms is still a venue which needs further investigation within an international scope. Here, my own teaching practice within a period of two semesters is reflected through the 61 male and female students' sharp and meticulous eyes, which is reflected in their written responses to the posed question at the end of their final exams, and some of my notes from their comments in each of their classes. The Constant Comparative method was then used to unearth students' comments and feedback on both my personality as an English-language teacher, and my teaching practice respectively.